Os caminhos de entrada do magnetismo animal no Brasil no século XIX Vianna - Vianna, Antonio Victor Morgado (2024)
The ideas of Franz Anton Mesmer (1734-1815) arrived in Brazil at the beginning of the 19th century, gaining followers from 1832 onwards. We study here how this journey took place in Brazilian lands, more specifically in Rio de Janeiro. We highlight more specifically the work of the pioneer Dr. Gamard (1783-1846) and the work of Dr. Eduardo Monteggia (? – 1883). Animal magnetism in Brazil was also resisted by academic institutions, but it acquired followers, being practiced during some decades of the 19th century. To achieve this objective, we analyzed articles and advertisements published in popular newspapers of the period, as well as documentation relating to the legalization of a Mesmerist Society and its published periodicals